Latency, Integration, and Reactivation of Human Herpesvirus-6 - Pantry, Shara N. (Viruses, 2017)
Human herpesvirus-6A (HHV-6A) and human herpesvirus-6B (HHV-6B) are two closely related viruses that infect T-cells. Both HHV-6A and HHV-6B possess telomere-like repeats at the terminal regions of their genomes that facilitate latency by integration into the host telomeres, rather than by episome formation. In about 1% of the human population, human herpes virus-6 (HHV-6) integration into germline cells allows the viral genome to be passed down from one generation to the other; this condition is called inherited chromosomally integrated HHV-6 (iciHHV-6). This review will cover the history of HHV-6 and recent works that define the biological differences between HHV-6A and HHV-6B. Additionally, HHV-6 integration and inheritance, the capacity for reactivation and superinfection of iciHHV-6 individuals with a second strain of HHV-6, and the role of hypomethylation of human chromosomes during integration are discussed. Overall, the data suggest that integration of HHV-6 in telomeres represent a unique mechanism of viral latency and offers a novel tool to study not only HHV-6 pathogenesis, but also telomere biology. Paradoxically, the integrated viral genome is often defective especially as seen in iciHHV-6 harboring individuals. Finally, gaps in the field of HHV-6 research are presented and future studies are proposed.